2020
DOI: 10.3389/fmars.2020.00094
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Assessment of a Black Rockfish, Sebastes schlegelii, Stock Enhancement Program in Lidao Bay, China Based on Mitochondrial and Nuclear DNA Analysis

Abstract: The black rockfish Sebastes schlegelii is a commercially important fish species for marine fishery stock enhancement in Asia. This work aimed to evaluate the potential genetic impacts of releasing hatchery-reared juvenile black rockfish on wild stock in Lidao Bay, China. A partial sequence of the mitochondrial DNA (mtDNA) control region and 38 microsatellite DNA loci were used to assess the genetic impact. The haplotype diversity parameter (h) and nucleotide diversity parameter (π) in hatcheryreleased stock we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
(60 reference statements)
2
8
1
Order By: Relevance
“…We observed that the S. schlegelii population showed relatively high genetic diversities before and after stock enhancement. Similar results have been reported in the Shandong peninsula, China (Wang et al, 2020). There was no significant difference in Na, Ne-allele and Ho between different stocks but the hatcheryreared stock, RA2019, exhibited a significantly lower Ar value than NA2019, after sequential Bonferroni correction (P < 0.05).…”
Section: Assessment Of the Potential Genetic Impactsupporting
confidence: 85%
See 1 more Smart Citation
“…We observed that the S. schlegelii population showed relatively high genetic diversities before and after stock enhancement. Similar results have been reported in the Shandong peninsula, China (Wang et al, 2020). There was no significant difference in Na, Ne-allele and Ho between different stocks but the hatcheryreared stock, RA2019, exhibited a significantly lower Ar value than NA2019, after sequential Bonferroni correction (P < 0.05).…”
Section: Assessment Of the Potential Genetic Impactsupporting
confidence: 85%
“…However, little research had evaluated the impacts on wild S. schlegelii populations. We only found that Wang et al (2020) reported that no marked decrease in the hatchery-released stock, low but significant differentiation between the hatchery-released and wild stocks, as well as the wild stock before enhancement and the mixed stock after enhancement in Lidao bay, Shandong peninsula. Aside from the above enhancement events, there has been no release of S. schlegelii in the Liaodong peninsula before 2019.…”
Section: Introductionmentioning
confidence: 68%
“…In addition to directly increasing the biomass of wild fish stocks, stock enhancement helps local stocks to maintain self-sustainable development [3]. Stock enhancement programs have been widely applied for decades over 300 species, such as flathead grey mullet (Mugil cephalus), silver carp (Hypophthalmichthys molitrix) and Korean rockfish (Sebastes schlegelii) [4][5][6][7]. In China, about 95 billion individuals composed of marine fish, shrimp and scallops were released into coastal regions during 2004-2013 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Stock enhancement programs have been widely applied for decades over 300 species, such as flathead grey mullet (Mugil cephalus), silver carp (Hypophthalmichthys molitrix) and Korean rockfish (Sebastes schlegelii) [4][5][6][7]. In China, about 95 billion individuals composed of marine fish, shrimp and scallops were released into coastal regions during 2004-2013 [7]. Nevertheless, negative genetic effects of hatchery-released juveniles on natural populations have been reported in some fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Members of Sebastes generally occur in cold-temperate and boreal waters (Wourms 1991;Mecklenburg et al 2002;Hyde and Vetter 2007), except for four species residing in the North Atlantic and two species being found in the Southern Hemisphere (Chen 1971;Rocha-Olivares et al 1999;Garabana 2005;Hyde and Vetter 2007). In addition, rockfishes are economically important species, especially in temperate regions (Muto et al 2018;Wang et al 2020). The distributions of rockfishes in the Northern Hemisphere are generally present from northern Japan and the waters of Alaska to California (Robins et al 1980;Wourms 1991).…”
Section: Introductionmentioning
confidence: 99%